2001
DOI: 10.1002/jcb.1084
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 1 promoter polymorphism and response to type 1 interferon

Abstract: The clinical success of interferon-treatment has been found to vary in different individuals. To explain this, we hypothesized that responses to type 1 interferons could be partly determined by interferon regulatory factor-1 gene transcription, because the latter is an important transcription factor in the interferon system. We demonstrated that the antiproliferative effect of type 1 interferons on human liver cancer cells correlates with levels of transcription of the interferon regulatory factor-1 gene in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…In the IRF-1 -/-NOD mouse, insulitis and diabetes were decreased accompanied by an increased survival [21]. Additional studies have suggested a role of IRF-1 and IFN-regulated genes in mediating human lupus [22][23][24]. Based on the knowledge that IRF-1 modulates inflammatory mediator production, we sought to determine whether IRF-1 gene deletion alters the severity of lupus nephritis in MRL/lpr mice.…”
mentioning
confidence: 99%
“…In the IRF-1 -/-NOD mouse, insulitis and diabetes were decreased accompanied by an increased survival [21]. Additional studies have suggested a role of IRF-1 and IFN-regulated genes in mediating human lupus [22][23][24]. Based on the knowledge that IRF-1 modulates inflammatory mediator production, we sought to determine whether IRF-1 gene deletion alters the severity of lupus nephritis in MRL/lpr mice.…”
mentioning
confidence: 99%
“…The genotype and allelic frequencies of each SNP were calculated and depicted in Table 2. Twenty-seven of these SNPs have been previously reported either in publications or by the International Human Genome Sequencing Consortium through the NCBI-based SNP database (Database1;Database2;Donn et al 2001;Nakao et al 2001;Noguchi et al 2000;Saito et al 2001Saito et al , 2002. A number of previously reported SNPs were not observed in the subjects from this study, including 5551T/G, 4950A/G, 5558T/C, 5636G/A, 7662C/-and 6355G/A, demonstrating the high degree of IRF-1 genetic polymorphism in different ethnic populations.…”
Section: Resultsmentioning
confidence: 99%
“…Beside the well-studied different ''GT'' dinucleotides repeats in intron 7 of IRF-1, 31 single nucleotide polymorphisms (SNPs) in IRF-1 have been identified in human subjects or cell lines by other researchers (Database1;Database2;Donn et al 2001;Nakao et al 2001;Noguchi et al 2000;Saito et al 2001Saito et al , 2002. Due to the potential role that IRF-1 may play in HIV-1 replication and its importance in the antiviral immune response, it is important to identify genetic polymorphisms in IRF-1 and determine if these mutations result in coding changes in expressed IRF-1 protein.…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al showed the promoter activity of an IRF-1 promoter with the -415C/-410A/-300A haplotype was higher than that of one with the -415A/-410G/-300G haplotype [17,18]. Donn et al reported that IRF-1 3=-UTR polymorphisms might confer susceptibility to JIA and suggested that 3=-UTR polymorphisms could affect IRF-1 mRNA stability [12].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, IRF-1 promoter functional polymorphisms have been found to be associated with antiviral activity against hepatitis C infection [17,18], and the 3=-untranslated region (UTR) polymorphism was suggested to be associated with disease susceptibility to JIA [12].…”
Section: Introductionmentioning
confidence: 99%